Las credenciales de los posgrados en las universidades públicas argentinas - Cardinaux, Nancy (2018)
The main objective of this article is to show a description of the present Postgraduate Studies at public Universities in Argentina, focusing on the low graduation rates they reach. As this topic has not been an object of great attention by educational investigation, we only count with some statistics data and isolated pieces of work, whose interpretation must set up a dialogue between the representations of the actors at this level of the University system. Specializations, Masters and Doctorates are addressed from their current regulations to the previous ones, dating from 1990; paying special attention to the needed requirements for the Final Degree Project, which appears on the limited reading material we count with and on the surveyed students, teachers and authorities representations, as the instance where the postgraduate studies are discontinued. Therefore, the low graduation level is related to all the difficulties in carrying out the Final Degree Project demanded by the Postgrades. In view of this constant, it will be listed below, the reasons why postgraduate students themselves, claim as the major difficulties they have faced to get their degrees, specifying some proper to the Legal field.